2015
DOI: 10.1111/apt.13288
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of certolizumab pegol for Crohn's disease in clinical practice

Abstract: SUMMARY BackgroundCertolizumab pegol (CZP) is Food and Drug Administration (FDA)-approved to treat Crohn's disease (CD). However, the efficacy and safety of CZP outside clinical trials are not well established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In another study, a higher proportion of older patients [>60 years] discontinued due to infections and a lower proportion due to loss of response compared with younger patients [<60 years]) . Non‐compliance or poor compliance as a reason for discontinuation was considered only in two CD studies, showing that only a small proportion of patients discontinued directly due to a reason categorized as issues with compliance (0.5%‐3.0% of patients; studies did not define compliance adequately to determine whether these cases were driven by patient preference) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, a higher proportion of older patients [>60 years] discontinued due to infections and a lower proportion due to loss of response compared with younger patients [<60 years]) . Non‐compliance or poor compliance as a reason for discontinuation was considered only in two CD studies, showing that only a small proportion of patients discontinued directly due to a reason categorized as issues with compliance (0.5%‐3.0% of patients; studies did not define compliance adequately to determine whether these cases were driven by patient preference) …”
Section: Resultsmentioning
confidence: 99%
“…In addition, many patients experienced dose escalations. In the first year of therapy, 8%‐35% of patients experienced dose escalation of the index therapy (four studies) and 17%‐40% of patients experienced dose escalation within the first 2 years of index therapy (two studies) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, retrospective long-term data on the efficacy of CZP were reported and identified early age of CD manifestation, previous primary non-response to adalimumab, and presence of perianal fistulizing disease as negative predictors of response [36] . However, these patients represent a highly selected collective from a single large US tertiary referral center.…”
Section: Discussionmentioning
confidence: 99%
“…This also favors an increase in its half-life to two weeks. Results from some studies showed clinical benefits in patients refractory to other biological therapies [58]. Earlier studies showed more effectiveness when it is used as first-line agent [51].…”
Section: Anti-tnf-α Antibodies In Current Ibd Therapymentioning
confidence: 99%